2019
DOI: 10.4254/wjh.v11.i9.678
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhotic patients and older people

Abstract: BACKGROUNDDespite being the world’s most widely used system for staging and therapeutic guidance in hepatocellular carcinoma (HCC) treatment, the Barcelona clinic liver cancer (BCLC) system has limitations, especially regarding intermediate-grade (BCLC-B) tumors. The recently proposed Hong Kong liver cancer (HKLC) staging system appears useful but requires validation in Western populations.AIMTo evaluate the agreement between BCLC and HKLC staging on the management of HCC in a Western population, estimating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 202 publications
1
16
0
1
Order By: Relevance
“…HCC and cirrhosis had the highest association, and produced the following comorbidity pattern: HCC, cirrhosis, chronic viral hepatitis B, portal hypertension, ascites, hypersplenism, peritonitis and other common complications of cirrhosis. Previous comorbidity studies on cirrhosis revealed that portal hypertension, ascites and other above diseases are common comorbidities of cirrhosis [31,32]. Compared with the literature [33,34], our study reports a high rate of HCC without associated cirrhosis.…”
Section: Discussionsupporting
confidence: 38%
“…HCC and cirrhosis had the highest association, and produced the following comorbidity pattern: HCC, cirrhosis, chronic viral hepatitis B, portal hypertension, ascites, hypersplenism, peritonitis and other common complications of cirrhosis. Previous comorbidity studies on cirrhosis revealed that portal hypertension, ascites and other above diseases are common comorbidities of cirrhosis [31,32]. Compared with the literature [33,34], our study reports a high rate of HCC without associated cirrhosis.…”
Section: Discussionsupporting
confidence: 38%
“…On the one hand, this study shows that being older is a risk factor for frailty and prefrailty in patients with cirrhosis, which will increase the incidence of complications and reduce the quality of life. On the other hand, studies have shown that being older is a risk factor for death in patients with cirrhosis [24]. So we should pay more attention to elderly patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…The unsteady rates of development of liver damage under similar risk factors as well as the variability in the pathogenesis of HBV infection demonstrate that the molecular mechanism of HBV-induced cirrhosis is not fully understood. Recently, a number of functional genetic polymorphisms that likely increase the risk of liver fibrosis progression were described, which, together with other external factors such as alcohol intake, body mass index (BMI), diabetes, or hepatitis could be helpful in the determination of risk profile for the individual patient [19][20][21][22][23][24]. Moreover, host genetic background is undoubtedly involved in the development of HBV-related liver diseases [25].…”
Section: Discussionmentioning
confidence: 99%